Studi Hubungan Interaksi Sosial Terhadap Tingkat Kesepian Lansia - Witon, Witon; Permatasari, Leya Indah; Akbar, Rizaluddin (Institut Citra Internasional, 2024)
The social service home for the elderly in Klampok Brebes faces challenges in the social interaction of the elderly within it. Some elderly people actively interact, have social networks, and feel comfortable in the nursing home environment. However, there are also elderly people who are less enthusiastic about interacting, feel bored, and are even indifferent to the people around them. The existence of conflict between the elderly and the formation of groups within the orphanage can be the main cause of the lack of social interaction, this can trigger the elderly to experience feelings of loneliness. The aim of this research is to determine the relationship between social interaction and loneliness for elderly people living in the Klampok Brebes Social Services Home for the Elderly. This type of research is quantitative research with a cross sectional design. Data were collected using the Social Interaction questionnaire and the UCLA Loneliness Scale Version 3. The research population was 56 respondents. The sampling technique was total sampling with a total of 56 respondents. Statistical tests use Spearman Rank. The research tool is a structured questionnaire with a Likert scale. The results of the analysis based on the Spearman Rank test show that the p value (0.000) < 0.05 means that there is a significant relationship between social interaction and loneliness of the elderly at the Klampok Brebes Elderly Social Services Home.